Effect of the addition of functionalized TiO2 nanotubes and nanoparticles on properties of experimental resin composites - Freitas Guimaraes, Genine Moreira de; Bronze-Uhle, Erika Soares; Lisboa-Filho, Paulo Noronha [UNESP]; Piovezan Fugolin, Ana Paula; Sanches Borges, Ana Flavia; Gonzaga, Carla Castiglia; Pfeifer, Carmem Silvia; Furuse, Adilson Yoshio (Elsevier B.V., 2020)
Objective. To evaluate the influence of the addition of functionalized and non-functionalized TiO2 nanostructures on properties of a resin composite. Methods. TiO2 nanostructures were synthesized and functionalized, using 3(aminopropyl)triethoxysilane (APTMS) and 3-(trimethoxysilyl)propyl methacrylate (TSMPM). Characterizations were performed with XRD, EDS, TEM, and TGA. Resin composites containing Bis-GMA/TEGDMA, CQ, DABE, and barium-aluminum silicate glass were produced according to TiO2 nanostructure (nanotube or nanoparticle), concentration (0.3 or 0.9 wt%), and functionalization (APTMS or TSMPM). The resin composite without nanostructures was used as control. The amount of fillers was kept constant at 78.3 wt% for all materials. The degree of conversion (DC at 0 h and 24 h), maximum polymerization rate (Rp(max)), and Knoop microhardness (KHN before and after ethanol softening) were evaluated. Data were analyzed with two-way ANOVA with repeated measures and Tukey's HSD (a = 0.05). Results. TGA results demonstrated that functionalizations were effective for both nanostructures. For DC, resin composites, time and interaction effect were significant (p < 0.001). Higher DC was found for 0.3-wt%-functionalized-nanotubes at 24 h. For nanoparticles, only 0.9-wt%-non-functionalized and 0.3-wt%-APTMS-functionalized showed DC similar to the control and all other groups showed higher DC (p < 0.05). Rpmax was higher for 0.3-wt%APTMS-nanotubes, which corresponded to higher DC after 24 h. The lowest Rpmax occurred for 0.9-wt%-TSMPM-nanotubes, which showed smaller DC at 0 h. For KHN, resin composites, ethanol softening and interaction effect were significant (p < 0.001). KHN decreased after ethanol softening all groups, except for 0.3-wt%-TSMPM-nanotubes, 0.9-wt%-TSMPMnanotubes, and 0.3-wt%-non-functionalized-nanoparticles. Conclusion. The resin with 0.3-wt%-TSMPM-nanotubes showed higher DC after 24 h, while being the most stable material after the ethanol softening. Significance. The addition of functionalized TiO2 nanostructures in resin-based materials may improve the properties of the material. (C) 2020 The Academy of Dental Materials. Published by Elsevier Inc. All rights reserved.
Keywords: Titanium dioxide; Nanostructures; Functionalization; Polymer structure; Methacrylates